High-dispersion non-oxidation superfine nano-particles and preparation method thereof
By loading micron-scale metal or silicon particles on a carbon substrate and performing carbon heat pulse treatment, the problem of easy agglomeration and oxidation of ultrafine metal nanoparticles during the preparation process is solved, and ultrafine nanosized in high dispersion and oxidation-free state is achieved Particle preparation maintains the high specific surface area and high activity of the nanoparticles.
Patent Information
- Application Number
- CN202411634345.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art can easily lead to particle agglomeration and oxidation when preparing ultrafine metal nanoparticles, resulting in the loss of the advantages of nanoparticles such as high specific surface area and high activity.
Highly dispersed, non-oxidized ultrafine nanoparticles were prepared by loading micron-scale metal particles or silicon particles on a carbon substrate and subjecting carbon heat pulse treatment. The method includes loading micron-scale particles on a carbon substrate and then processing in a carbon-heat pulse device to control parameters such as voltage, current, temperature and time of the carbon-heat pulse to prepare spherical nanoparticles with adjustable diameters.
The high dispersion and oxidation-free state of nanoparticles are achieved, the high specific surface area and high activity of nanoparticles are maintained, and the preparation process is controllable, which can adjust the diameter and dispersion of nanoparticles.
Smart Images

Figure CN119501084A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to highly dispersed non-oxidized ultrafine nanoparticles and a preparation method thereof. Background Art
[0002] Metal nanoparticles are widely used in energy storage, catalysis, biomedicine and other fields. Current methods for preparing ultrafine metal nanoparticles mainly include top-down techniques, such as pyrolysis, grinding and radiation, which involve the use of physical, chemical or mechanical processes to decompose bulk materials into nanoparticles. Although these methods are relatively simple, they usually lead to nanoparticle agglomeration and increased introduction of impurities; secondly, bottom-up methods, such as chemical vapor deposition, aim to synthesize nanoparticles by assembling atom by atom, thereby better controlling the size and shape, but the particles in this method are easily oxidized and the equipment conditions are demanding. In summary, the preparation of ultrafine metal nanoparticles faces the challenges of easy agglomeration and oxidation of particles, resulting in the loss of advantages of metal nanoparticles such as high specific surface area and high activity.
[0003] At present, in order to ensure that the oxidation rate of nanoparticles is low, the re-dispersion of agglomerated particles usually requires a two-stage treatment, the first stage is heat treated in an oxidizing atmosphere, and the second stage is carried out in a reducing atmosphere, usually at a heating rate of 10 ° C / min to 600 ~ 1000 K, through the continuous cycle of this process, to achieve a significant reduction in particle size, the degree of dispersion of the particles in this method depends on the size of the agglomerated particles, and larger materials require longer time. However, the ability of this method to disperse nanoparticles is limited because continuous and excessive heat input will offset the effectiveness of redispersion.
[0004] Therefore, starting from the preparation method of nanoparticle materials, inventing a preparation method for highly dispersed, oxidation-free ultrafine metal nanoparticles is an important guarantee for realizing the photovoltaic application of metal nanoparticles. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a highly dispersed non-oxidized ultrafine nanoparticle and a preparation method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing highly dispersed non-oxidized ultrafine nanoparticles comprises the following steps:
[0008] (1) loading micron-sized metal particles or micron-sized silicon particles on a carbon substrate to obtain a precursor A;
[0009] (2) Precursor A is subjected to carbon thermal pulse to obtain nanoparticles.
[0010] As a preferred embodiment of the present invention, in the step (1), the micron-sized metal particles or micron-sized silicon particles are loaded on the carbon substrate by a wet method, a dry method or a spray method.
[0011] As a preferred embodiment of the present invention, the sizes of the micron-sized metal particles and micron-sized silicon particles are both 1-1000 microns.
[0012] As a preferred embodiment of the present invention, the micron-sized metal particles are aluminum, nickel, copper, germanium, silver or tin.
[0013] As a preferred embodiment of the present invention, the carbon substrate is at least one of carbon cloth, carbon felt, carbon paper, graphite paper, carbon nanofiber paper, graphene film, graphite sheet, graphite crucible, and carbon fiber products.
[0014] As a preferred embodiment of the present invention, the carbon thermal pulse has a voltage of 1-200V, a current of 1-200A, a temperature of 800-2500°C, a time of 0.01-60s, a cooling rate greater than 500°C / s, and an inert gas atmosphere.
[0015] More preferably, the carbon thermal pulse has a voltage of 40 to 100 V, a current of 20 to 60 A, a temperature of 800 to 1700° C., a time of 0.01 to 1 s, a cooling rate greater than 500° C. / s, and an inert gas atmosphere.
[0016] The inert gas is argon, nitrogen, carbon dioxide, a hydrogen-argon mixture or a hydrogen-nitrogen mixture.
[0017] The present invention also claims to protect the highly dispersed non-oxidized ultrafine nanoparticles prepared by the method for preparing the highly dispersed non-oxidized ultrafine nanoparticles.
[0018] As a preferred embodiment of the present invention, the nanoparticles are spherical with a diameter of 10-500 nm.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention uses micron-sized metal particles or micron-sized silicon particles as raw materials, and by controlling the parameters of the carbon thermal pulse, the purpose of adjusting the diameter, dispersibility and oxidation degree of the nanoparticles is achieved, and finally non-oxidized spherical nanoparticles with adjustable diameter and good dispersibility are formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 These are SEM images of silicon particles and silicon nanoparticles with a particle size of 1 to 1000 microns in Example 1, wherein (a) is a morphology image of silicon particles with a particle size of 1 to 1000 microns, (b) is a low-magnification SEM image of silicon nanoparticles, and (c) is a high-magnification SEM image of silicon nanoparticles.
[0021] Figure 2 These are SEM images of aluminum particles and aluminum nanoparticles with a particle size of 1 to 1000 microns in Example 2, wherein (a) is a morphology image of aluminum particles with a particle size of 1 to 1000 microns, and (b) is a morphology image of aluminum nanoparticles.
[0022] Figure 3 These are SEM images of nickel particles and nickel nanoparticles with a particle size of 1 to 1000 microns in Example 3, wherein (a) is a morphology image of nickel particles with a particle size of 1 to 1000 microns, and (b) is a morphology image of nickel nanoparticles.
[0023] Figure 4 These are SEM images of copper particles and copper nanoparticles with a particle size of 1 to 1000 microns in Example 4, wherein (a) is a morphology image of copper particles with a particle size of 1 to 1000 microns, (b) is a low-magnification SEM image of copper nanoparticles, and (c) is a high-magnification SEM image of copper nanoparticles.
[0024] Figure 5 These are SEM images of germanium particles and germanium nanoparticles with a particle size of 1 to 1000 microns in Example 5, wherein (a) is a morphology image of germanium particles with a particle size of 1 to 1000 microns, and (b) is a morphology image of germanium nanoparticles.
[0025] Figure 6 These are SEM images of silver particles and silver nanoparticles with a particle size of 1 to 1000 microns in Example 6, wherein (a) is a morphology image of silver particles with a particle size of 1 to 1000 microns, and (b) is a morphology image of silver nanoparticles.
[0026] Figure 7 These are SEM images of tin particles and tin nanoparticles with a particle size of 1 to 1000 microns in Example 7, wherein (a) is a morphology image of tin particles with a particle size of 1 to 1000 microns, and (b) is a morphology image of tin nanoparticles. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0028] Example 1
[0029] A method for preparing highly dispersed non-oxidized ultrafine silicon nanoparticles comprises the following steps:
[0030] (1) loading silicon particles with a particle size of 1 μm on carbon cloth by a wet method to obtain a precursor A;
[0031] (2) Precursor A was placed in a carbon thermal pulse device to prepare silicon nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 40 V, the current was 20 A, the atmosphere was an argon inert environment, the temperature was 1600 ° C, the time was 0.01 s, and the cooling rate was greater than 500 ° C / s to prepare spherical silicon nanoparticles with a diameter of about 80 nm.
[0032] The morphology of silicon raw materials and silicon nanoparticles is as follows Figure 1 As shown, the silicon raw material is irregularly shaped micron-sized particles with a size of about 1 to 2 microns. The prepared spherical silicon nanoparticles have a size of 50 to 90 nm, good dispersibility, and an oxygen content of less than 1 ppm.
[0033] Example 2
[0034] A method for preparing highly dispersed non-oxidized ultrafine aluminum nanoparticles comprises the following steps:
[0035] (1) Aluminum particles with a particle size of 40 μm are loaded on carbon felt by a wet method to obtain a precursor A;
[0036] (2) Precursor A was placed in a carbon thermal pulse device to prepare aluminum nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 50 V, the current to be 50 A, the atmosphere to be an argon inert environment, the temperature to be 1200 ° C, the time to be 1 s, and the cooling rate to be greater than 500 ° C / s to prepare spherical aluminum nanoparticles with a diameter of about 200 nm.
[0037] The morphology of aluminum raw materials and aluminum nanoparticles is as follows Figure 2 As shown, the aluminum raw material is irregular in shape and about 30 to 50 microns in size; the prepared aluminum nanoparticles are spherical, 100 to 200 nm in size, have good dispersibility, and an oxygen content of less than 10 ppm.
[0038] Example 3
[0039] A method for preparing highly dispersed non-oxidized ultrafine nickel nanoparticles comprises the following steps:
[0040] (1) nickel particles with a particle size of 60 μm are loaded on carbon felt by a wet method to obtain a precursor A;
[0041] (2) Precursor A was placed in a carbon thermal pulse device to prepare nickel nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 100 V, the current was 60 A, the atmosphere was an argon inert environment, the temperature was 1700 ° C, the time was 0.05 s, and the cooling rate was greater than 500 ° C / s to prepare spherical nickel nanoparticles with a diameter of 100 to 200 nm.
[0042] The morphology of nickel raw materials and nickel nanoparticles is as follows Figure 3As shown, the shape of the nickel raw material is irregularly dendritic and the size is about 40 to 70 microns; the prepared nickel nanoparticles are spherical and the size is 100 to 200 nm, with good dispersibility and an oxygen content of less than 2 ppm.
[0043] Example 4
[0044] A method for preparing highly dispersed non-oxidized ultrafine copper nanoparticles comprises the following steps:
[0045] (1) copper particles with a particle size of 50 μm are loaded on carbon felt by a wet method to obtain a precursor A;
[0046] (2) Precursor A was placed in a carbon thermal pulse device to prepare copper nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 40 V, the current was 50 A, the atmosphere was an argon inert environment, the temperature was 1200 ° C, the time was 0.05 s, and the cooling rate was greater than 500 ° C / s to prepare spherical copper nanoparticles with a diameter of about 300 nm.
[0047] The morphology of copper raw materials and copper nanoparticles is as follows Figure 4 As shown, the copper raw material is spherical particles of several tens of microns and a size of about 40 to 60 microns; the prepared copper nanoparticles are spherical and 200 to 500 nm in size, with good dispersibility and an oxygen content of less than 2 ppm.
[0048] Example 5
[0049] A method for preparing highly dispersed non-oxidized ultrafine germanium nanoparticles comprises the following steps:
[0050] (1) loading germanium particles with a particle size of 50 μm on carbon felt by a wet method to obtain a precursor A;
[0051] (2) Precursor A is placed in a carbon thermal pulse device to prepare germanium nanoparticles. The voltage of the carbon thermal pulse process is controlled to be 50 V, the current is 40 A, the atmosphere is an argon inert environment, the temperature is 1200°C, the time is 0.02 s, and the cooling rate is greater than 500°C / s to prepare spherical germanium nanoparticles with a diameter of about 100 nm.
[0052] The morphology of germanium raw materials and germanium nanoparticles is as follows Figure 5 As shown, the germanium raw material is irregular in shape and about 50 to 60 microns in size; the prepared germanium nanoparticles are spherical, 100 to 200 nm in size, with good dispersibility and an oxygen content of less than 2 ppm.
[0053] Example 6
[0054] A method for preparing highly dispersed non-oxidized ultrafine silver nanoparticles comprises the following steps:
[0055] (1) silver particles with a particle size of 3 μm are loaded on carbon felt by a wet method to obtain a precursor A;
[0056] (2) Precursor A was placed in a carbon thermal pulse device to prepare silver nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 40 V, the current was 40 A, the atmosphere was an argon inert environment, the temperature was 1200 ° C, the time was 0.02 s, and the cooling rate was greater than 500 ° C / s to prepare spherical silver nanoparticles with a diameter of about 200 nm.
[0057] The morphology of silver raw materials and silver nanoparticles is as follows Figure 6 As shown, the silver raw material has an irregular shape and a size of about 3 to 5 microns; the prepared silver nanoparticles are spherical, 200 nm in size, have good dispersibility, and an oxygen content of less than 1 ppm.
[0058] Example 7
[0059] A method for preparing highly dispersed non-oxidized ultrafine tin nanoparticles comprises the following steps:
[0060] (1) loading tin particles with a particle size of 40 μm on carbon felt by a wet method to obtain a precursor A;
[0061] (2) Precursor A was placed in a carbon thermal pulse device to prepare tin nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 30 V, the current was 30 A, the atmosphere was an argon inert environment, the temperature was 800 ° C, the time was 0.02 s, and the cooling rate was greater than 500 ° C / s to prepare spherical tin nanoparticles with a diameter of about 200 nm.
[0062] The morphology of tin raw materials and tin nanoparticles is as follows Figure 7 As shown, the tin raw material is in the shape of long strips and has a size of about 30 to 50 microns; the prepared tin nanoparticles are spherical and have a size of 100 to 200 nm, have good dispersibility, and have an oxygen content of less than 5 ppm.
[0063] Comparative Example 1
[0064] A method for preparing highly dispersed non-oxidized ultrafine copper nanoparticles comprises the following steps:
[0065] (1) Copper chloride is dissolved in water to obtain a solution, which is then loaded on carbon felt by a wet method to obtain a precursor A.
[0066] (2) Precursor A was placed in a carbon thermal pulse device to prepare copper nanoparticles. The voltage of the carbon thermal pulse process was controlled to be 20 V, the current was 20 A, the atmosphere was an argon inert environment, the temperature was 1100 ° C, the time was 0.01 s, and the cooling rate was greater than 500 ° C / s. Spherical metal oxide particles with a size of about 10 to 50 nm were prepared with good dispersibility. Single metal nanoparticles could not be synthesized.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing highly dispersed non-oxidized ultrafine nanoparticles, characterized in that: The steps include: (1) loading micron-sized metal particles or micron-sized silicon particles on a carbon substrate to obtain a precursor A; (2) Precursor A is subjected to carbon thermal pulse to obtain nanoparticles.
2. The method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to claim 1, characterized in that: In the step (1), micron-sized metal particles or micron-sized silicon particles are loaded on a carbon substrate by a wet method, a dry method or a spray method.
3. The method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to claim 1, characterized in that: The sizes of the micron-sized metal particles and micron-sized silicon particles are both 1-1000 microns.
4. The method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to claim 1, characterized in that: The micron-sized metal particles are aluminum, nickel, copper, germanium, silver or tin.
5. The method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to claim 1, characterized in that: The carbon substrate is at least one of carbon cloth, carbon felt, carbon paper, graphite paper, carbon nanofiber paper, graphene film, graphite sheet, graphite crucible, and carbon fiber products.
6. The method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to claim 1, characterized in that: The carbon thermal pulse has a voltage of 1 to 200 V, a current of 1 to 200 A, a temperature of 800 to 2500° C., a time of 0.01 to 60 s, a cooling rate greater than 500° C. / s, and an inert gas atmosphere.
7. The method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to claim 1, characterized in that: The carbon thermal pulse has a voltage of 40 to 100 V, a current of 20 to 60 A, a temperature of 800 to 1700° C., a time of 0.01 to 1 s, a cooling rate greater than 500° C. / s, and an inert gas atmosphere.
8. Highly dispersed non-oxidized ultrafine nanoparticles prepared by the method for preparing highly dispersed non-oxidized ultrafine nanoparticles according to any one of claims 1 to 7.
9. The highly dispersed non-oxidized ultrafine nanoparticles according to claim 8, characterized in that: The nanoparticles are spherical and have a diameter of 10-500 nm.
Citation Information
Patent Citations
Method of manufacturing composite anode material and composite anode material applied to lithium secondary battery
CN111799449A
Method for preparing silicon nanowire material and application
CN117361542A
Method for rapidly and controllably preparing superfine metal nanocrystal / nanocarbon composite film
CN117568759A
Nanoparticles and systems and methods for synthesizing nanoparticles through thermal shock
US20180369771A1